2023
DOI: 10.5194/gmd-16-977-2023
|View full text |Cite
|
Sign up to set email alerts
|

SERGHEI (SERGHEI-SWE) v1.0: a performance-portable high-performance parallel-computing shallow-water solver for hydrology and environmental hydraulics

Abstract: Abstract. The Simulation EnviRonment for Geomorphology, Hydrodynamics, and Ecohydrology in Integrated form (SERGHEI) is a multi-dimensional, multi-domain, and multi-physics model framework for environmental and landscape simulation, designed with an outlook towards Earth system modelling. At the core of SERGHEI's innovation is its performance-portable high-performance parallel-computing (HPC) implementation, built from scratch on the Kokkos portability layer, allowing SERGHEI to be deployed, in a performance-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 166 publications
0
3
0
Order By: Relevance
“…In the future, it would be interesting to extend this modeling approach to bigger watersheds to test the overall run time, even considering more HPC‐enabled solutions to enhance the computational efficiency (Caviedes‐Voullième et al., 2023; Morales‐Hernández et al., 2021; Sharifian et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, it would be interesting to extend this modeling approach to bigger watersheds to test the overall run time, even considering more HPC‐enabled solutions to enhance the computational efficiency (Caviedes‐Voullième et al., 2023; Morales‐Hernández et al., 2021; Sharifian et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, nowadays, the use of high‐performance computing (HPC) is common and several 2D‐SWEs codes are developed using parallelization schemes. As a consequence, approaches based on both the message passing interface (MPI) or open multi‐processing, compatible with clusters composed of several central processing units and the general purpose graphics processing unit have been shown highly efficient, leading to a drastic reduction of the computational times (Buttinger‐Kreuzhuber et al., 2022; Carlotto et al., 2021; Caviedes‐Voullième et al., 2023; Dazzi et al., 2018; Morales‐Hernández et al., 2021; Noh et al., 2018; Sanders & Schubert, 2019; Vacondio et al., 2017; X. Xia et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the flooding of the Huangpu district is simulated with the SERGHEI-SWE model (Caviedes-Voullième et al, 2023). SERGHEI-SWE is an open-source, high-performance hydrodynamic model.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…GPU computing have dramatically reduced the computational cost for large-scale hydrodynamic simulations. Caviedes-Voullième et al (2023) has shown that using SERGHEI-SWE, for a computational domain with 0.5 million grid cells, hydrodynamic simulations on a workstation GPU remain faster than that on 128 CPU threads. Thus, SERGHEI-SWE with GPU computing capability is an ideal tool for completing massive flood simulation scenarios (e.g., the multiple random building collapse scenarios used in this study) within an acceptable time frame.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation